Perancangan Sistem Informasi Kemetrologian dalam Pendekatan Business Process Reengineering untuk Pelayanan Tera - Ari Dwi Yulianto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
For years, the calibration and re-calibration service in Metrology Units is still running manually using a lot of paper documents. This situation has led to some administrative problems and high occurrence of manual errors. Therefore, it required an information system to improve the management of data and information in the Metrology Units. The aim of the research is to propose a new business process and also to propose a design of metrological information system for management of data and information on the calibration and re-calibration service in Metrology Units. The development of this system is organized in the Business Process Reengineering framework to show the activities in the organization's business process changes. The result of the research shows that the proposed business process by utilizing the information system is able to meet the improvement objectives i.e. the average time of administration process is dropped by 41.6%, facilitate the need to retrieve past data and information easier, and it is able to make the management of data and information on the calibration and recalibration services become more efficient in terms of the use of resources such as documents, human resources, and time duration to complete the work.